2003
DOI: 10.1016/s0009-9236(03)00060-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of OATP-C (SLC21A6) and OAT3 (SLC22A8) genes: Consequences for pravastatin pharmacokinetics

Abstract: Certain commonly occurring single-nucleotide polymorphisms in OATP-C, such as T521C (Val174Ala), are likely to be associated with altered pharmacokinetics of pravastatin. Large clinical studies are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
398
7
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(439 citation statements)
references
References 36 publications
29
398
7
5
Order By: Relevance
“…Another functionally important SNP is 521T4C (rs4149056; V174A), SNP 524 in block 4. 8 In our study, SNP 524 Polymorphisms of drug transporters in three races S Endo et al Polymorphisms of drug transporters in three races S Endo et al Polymorphisms of drug transporters in three races S Endo et al Polymorphisms of drug transporters in three races S Endo et al was not associated with changes in any pharmacokinetic parameters. In addition to this, the SLCO1B1*1A (388A-521C), *1B (388G-521T), *5 (388A-521C) and *15 (388G-521C) haplotypes, 4 which were formed through these two SNPs, did not show any statistical significant associations (data not shown).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Another functionally important SNP is 521T4C (rs4149056; V174A), SNP 524 in block 4. 8 In our study, SNP 524 Polymorphisms of drug transporters in three races S Endo et al Polymorphisms of drug transporters in three races S Endo et al Polymorphisms of drug transporters in three races S Endo et al Polymorphisms of drug transporters in three races S Endo et al was not associated with changes in any pharmacokinetic parameters. In addition to this, the SLCO1B1*1A (388A-521C), *1B (388G-521T), *5 (388A-521C) and *15 (388G-521C) haplotypes, 4 which were formed through these two SNPs, did not show any statistical significant associations (data not shown).…”
Section: Discussionmentioning
confidence: 44%
“…Two aliquots of at least 0.7 ml of plasma each were removed, placed in screw-cap polypropylene tubes and immediately stored at À20 1C or below until the analysis. Blood samples were collected before and at 0.5, 1, 1.5, 2, 3, 4,6,8,12,16,24,36,48,60 and 72 h following each dose. The plasma concentrations of olmesartan were determined by a validated method of high-performance liquid chromatography with fluorescence detection.…”
Section: Sample Treatments and Pharmacokinetic Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Mwinyi et al 8 reported that the area under the concentration curve (0-6 h) in SLCO1B1*1a/*5 carriers (n ¼ 10) was 1.4-fold larger than that in SLCO1B1*1a/*1a carriers (n ¼ 10). Nishizato et al 6 reported that nonrenal clearances of pravastatin in SLCO1B1*1b/*15 carriers (n ¼ 9) and in SLCO1B1*15/*15 carriers (n ¼ 1) were 55 and 13%, respectively, of that in SLCO1B1*1b/*1b carriers (n ¼ 4). Therefore, although the Cell-surface biotinylation analysis was performed and OATP1B1 variants were detected by western blotting.…”
Section: T Furihata Et Almentioning
confidence: 99%
“…Several single-nucleotide polymorphisms (SNPs) have been identified in SLCO1B1 (Nozawa et al 2002;Tirona et al 2001), and some are reported to be associated with alterations in the pharmacokinetics of certain substrate drugs, including repaglinide (Niemi et al 2005a), fexofenadine (Niemi et al 2005b), pitavastatin (Chung et al 2005;Ieiri et al 2007), and pravastatin (Mwinyi et al 2004;Niemi et al 2004;Nishizato et al 2003). Particularly subjects having SLCO1B1*15 allele (possessing both 388A [G and 521T[C) showed elevated systemic exposure of pravastatin as compared to subjects without this allele (Niemi et al 2004;Nishizato et al 2003). In contrast, some reports indicated that SLCO1B1*1b allele (possessing 388A [G) showed enhanced transport activity of OATP1B1 as compared with wild-type allele (i.e., *1a allele) (Maeda et al 2006;Mwinyi et al 2004).…”
Section: Introductionmentioning
confidence: 99%